Pengaruh Citra Destinasi Dan Fasilitas Wisata Terhadap Kepuasan Wisatawan Beejay Bakau Resort (BJBR) Probolinggo - Mu'awanah, Risalatul; Elmas, Muhammad Syarif Hidayatullah; Hemawan, Dedi Joko (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research aims to find out whether destination image (X1) and tourist facilities (X2) have a partial effect on tourist satisfaction at BeeeJay Bakau Resort (BJBR) Probolinggo. The research method used is quantitative. The population in this study was 90 BJBR Probolinggo tourists using a simple random sampling technique with the hair formula. The data sources used in this research come from primary data and secondary data sources. Meanwhile, data collection methods are by means of questionnaires, interviews and documentation. The test results show that spatially, only tourist facilities have an influence on BJBR tourist satisfaction. Meanwhile, the results of simultaneous testing on both variables have a significant influence on tourist satisfaction. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value of 0.622, this means that 62.2% of the dependent variable of tourist satisfaction is influenced by the variables of destination image and tourist facilities. Meanwhile, the rest is influenced by other variables not included in this research